Contrastive Focus Particles In Kusaal - Abubakari, Hasiyatu (My University, 2019)
This paper presents and discusses the particles used in expressing contrastive focus in Kusaal, a Gur language spoken in Ghana, Burkina Faso and Togo. Contrary to the earlier claim made by Abubakari (2011) that focus is morphologically null in the language, the particles kà, ń and nɛ́ are identified as contrastive focus markers in Kusaal. The particle kà is limited to fronted focused items, whilst ń and nɛ́ are limited to in-situ focused constituents. Ex-situ focus always bears contrastive interpretation, hence the obligatory use of kà. In-situ focus is marked prosodically. However, the in-situ use of ń and nɛ́ correlates with a contrastive and exhaustive focus interpretation. To determine the validity of ń, nɛ́ and kà as contrastive focus particles, I subject them to various tests of exhaustivity from which I conclude that these are contrastive focus particles in the language.
Keywords: Kʋsaal; contrastive{\slash; focus particles